2021
DOI: 10.1016/j.eneco.2021.105569
|View full text |Cite
|
Sign up to set email alerts
|

A stakeholder analysis of investments in wind power electricity generation in Ontario

Abstract: This study uses an ex-post evaluation of the grid-connected wind projects in Ontario, Canada, to quantify the stakeholder impacts of such renewable energy projects. Our study includes a financial, economic and stakeholder analysis of these wind farms. The analysis sheds light on the distributional impacts that arise when there is a significant gap between the incentives created by the financial price paid for electricity generation and the economic value of the electricity generated. The analysis shows that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…If Ontario experiences a surplus of base-load generating capacity, further additions to base-load in the form of solar power may require removing a nuclear plant from operation and replacing it with a combination of renewable and gas-fired generation, yielding a net increase in emissions (seeMcKitrick (2013)). 15 This finding is comparable with those ofBahramian, Jenkins, and Milne (2021), who found that the environmental benefits of Ontario's wind power generation are only 11 percent of the net economic losses created by wind generation.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…If Ontario experiences a surplus of base-load generating capacity, further additions to base-load in the form of solar power may require removing a nuclear plant from operation and replacing it with a combination of renewable and gas-fired generation, yielding a net increase in emissions (seeMcKitrick (2013)). 15 This finding is comparable with those ofBahramian, Jenkins, and Milne (2021), who found that the environmental benefits of Ontario's wind power generation are only 11 percent of the net economic losses created by wind generation.…”
mentioning
confidence: 70%
“…We employ the Integrated Investment Appraisal approach developed byJenkins, Kuo, and Harberger (2019), a similar methodology used byBahramian, Jenkins, and Milne (2021), to evaluate the wind farms in Ontario, Canada.5 As of 2021, solar net metering has been the most popular type of installed capacity, with more than 3,000 participants across the province, totaling 66 megawatts (MWs).…”
mentioning
confidence: 99%
“…This methodology has been applied to analyze the distributional impacts of interventions in many different sectors. For example, it was applied in the analysis of the Yesilirmak Dam in North Cyprus [38] and the evaluation of wind farms in Ontario, Canada [39] The financial costs of the supply from the R.O. system at different capacity utilization levels provide information on the levelized cost of supplying water from the plant to provide water system reliability.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, [33] emphasized the distributional effects of a substantial disparity between the incentives established by the financial price paid for electricity generation and the economic value of the electricity produced in Canada. It was discovered that all participants in the electricity system experienced losses in this project, except the wind farm owners, who are privately owned.…”
Section: Literature Reviewmentioning
confidence: 99%